International-minded Leadership: Leading through Intercultural Understanding - Hamidah, H (2016)
The main purpose of this dissertation is to investigate the way school leaders in international school setting lead a multicultural group of teachers through intercultural understanding and their attainment to modeling the concept of international mindedness within the school community. To achieve this, I conducted a semi-structured interview as my data collection with ten school leaders who currently work at international schools across the continent of Asia, Australia and Europe. This study gathers data from current practices carried out by the school leaders in the international school and examines those practices against the literature available, to make a conclusion of how school leaders adhere to the concept of international mindedness. The result of this study confirms that leaders in international schools face unique demands and challenges that are related to ‘international features’ of international school, for example, leading a group of multicultural teachers. The findings from the gathered information show close relationship between the importance of the development of international mindedness and effective leadership in the setting of international schools. The findings also suggest further studies can be conducted to support the incorporation of international development in leadership practices through trainings and workshops.